Kinetic-hydrodynamic models considering climatic influence on the domestic sewage treatment by constructed wetlands in tropical country - Silva Júnior, Édio Damásio da; Souza, Marco Antonio Almeida de (Acta Scientiarum. Technology, 2023)
Typical constructed wetlands (CW) sizing methods in tropical countries rarely considers climate parameters as evapotranspiration (EPT) and rainfall (Ra), even though high levels of EPT and Ra can change the pollutant removal kinetic and Wastewater hydrodynamic. This paper aims to evaluate the climatic influences (EPT and Ra) on fit of several kinetic-hydrodynamic models used to describe the sewage organic matter removal in a real scale vertical (VSSF-CW) and horizontal (HSSF-CW) subsurface flow constructed wetland. Sewage quality (Biochemical Oxygen Demand - BOD and Chemical Oxygen Demand - COD) and sewage flow rates data were applied of First Order, Grau-Second Order, Monod, Monod Multi and Stover-Kincannon kinetic models, combined with ideal continuous stirred-tank reactor (CSTR) and plug-flow reactor (PF) hydrodynamic models. Monod, Monod Multi and Stover-Kincannon models (in CSTR) were more able to represent organic matter removal in CWs. Models considering EPT and Ra were more adequate or with no statistical difference compared with conventional models (that don´t consider EPT and Ra), except for BOD in VSSF-CW.